2006
DOI: 10.1109/tuffc.2006.1593373
|View full text |Cite
|
Sign up to set email alerts
|

Torsional vibrations of circular elastic plates with thickness steps

Abstract: Abstract-This paper presents a theoretical study of torsional vibrations in isotropic elastic plates. The exact solutions for torsional vibrations in circular and annular plates are first reviewed. Then, an approximate method is developed to analyze torsional vibrations of circular plates with thickness steps. The method is based on an approximate plate theory for torsional vibrations derived from the variational principle following Mindlin's series expansion method. Approximate solutions for the zeroth-and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…These 2D equations yield the exact solutions for zeroth-and first-order torsional modes in uniform plates without any correction factors [23].…”
Section: Torsional Vibrations Of Stepped Platesmentioning
confidence: 95%
See 3 more Smart Citations
“…These 2D equations yield the exact solutions for zeroth-and first-order torsional modes in uniform plates without any correction factors [23].…”
Section: Torsional Vibrations Of Stepped Platesmentioning
confidence: 95%
“…The remainder of this paper focuses on the circumferential motion, corresponding to torsional modes in the elastic plates [23]. The uncoupling of torsional modes from flexural modes allows pure in-plane motion of the resonator, which is advantageous for applications requiring immersion in or in contact with liquids [12].…”
Section: Two-dimensional Plate Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, no compressional waves are generated in the adjacent liquid, and the sensor response can be related to the liquid properties without concerning the liquid thickness. Previously we have demonstrated that energy-trapping torsional-mode vibrations can be excited in elastic plates by using an electromagnetic acoustic transducer (EMAT) [10,11]. In this paper, experiments are conducted to study effect of liquid thickness on the torsional-mode resonators, in comparison with thickness-shear mode.…”
Section: Introductionmentioning
confidence: 99%